The role of information display board in assessing and influencing the knowledge and perception of patients on dental radiography: an institution based prospective cohort study - Couppoussamy, Rajkumar; Sankaran, Sudhakar; Sundar, Shreenivas; Rahman, Nayeem Ur (International Journal Of Community Medicine And Public Health, 2022)
Background: Patients gain knowledge about dental radiography from various sources and this can attribute to their perception and attitude. There is a broad conception that the general public have much reservation about dental radiography. Methods: 300 randomly selected samples visiting as outpatients to oral radiology of our institution were selected for the study. A pilot-tested questionnaire containing 15 questions related to evaluation of knowledge and perception of dental radiography was given to the selected samples and asked to select their choice. Then an information display board related to dental radiography and radiation protection protocols was presented. Following which the questionnaire was redistributed and the study samples were asked to alter the choices of answers, if any. The data obtained were recorded and statistical analysis was done using Shapiro-Wilk and t-test. Results: Prior exposure to information display, 50% of the participants felt that the x-radiations are harmful and 36% believed that the benefits of diagnostic radiology do not outweigh the potential risk. After the exposure to displayed board containing information regarding dental radiography, 95% acknowledged that the radiographs play a vital role in diagnosis and 85% recognized that the benefits of radiography outweigh its risk. Conclusions: The findings of the study suggests that the radiology educational display board imparted better knowledge and acceptance of dental radiology protocols among the participants.